Perancangan Sistem Informasi Surat Pengantar Berbasis Website Menggunakan Rapid Application Development (RAD) - Sri Dianing Asri; Imam Bawafi (INFORMATION MANAGEMENT FOR EDUCATORS AND PROFESSIONALS : Journal of Information Management, 2023)
Making a cover letter is an important matter in the administrative process in society. RT 006 RW 013 is a community organization in the Duri Kosambi Village area, Cengkareng, West Jakarta Administrative City, and currently requires a system to simplify the process of making cover letters to provide fast service to its citizens. The design of this application was carried out using data collection methods in the form of observations and interviews which stated the conditions faced by residents in conventionally making cover letters, namely by visiting the head of the RT to propose making the cover letter. This method is deemed inefficient if the need for the cover letter is urgent and the RT head is not at his residence. In system development, the Rapid Application Development (RAD) method is applied in making this application with four stages, namely requirements planning, system design, development process and gathering feedback, and product implementation or completion. The design of this application also begins with an analysis of running business processes and produces an application for making a cover letter. The design of this application will simplify the process of making cover letters for residents and RT heads online and reduce the risk of losing a copy of the cover letter data. Keywords: information systems, website, cover letters, rapid application development